Long-lived tumor-associated macrophages in glioma. Issue 1 (25th September 2020) - Georgieva, Petya B; Mathivet, Thomas; Alt, Silvanus; Giese, Wolfgang; Riva, Matteo; Balcer, Marly; Gerhardt, Holger
Abstract: Background: The tumor microenvironment plays a major tumor-supportive role in glioma. In particular, tumor-associated macrophages (TAMs), which can make up to one-third of the tumor mass, actively support tumor growth, invasion, and angiogenesis. Predominantly alternatively activated (M2-polarized) TAMs are found in late-stage glioma in both human and mouse tumors, as well as in relapse samples from patients. However, whether tumor-educated M2 TAMs can actively contribute to the emergence and growth of relapse is currently debated. Methods: To investigate whether tumor-educated stromal cells remaining in the brain after surgical removal of the primary tumor can be long-lived and retain their tumor-supporting function, we developed a transplantation mouse model and performed lineage-tracing. Results: We discovered that macrophages can survive transplantation and stay present in the tumor much longer than previously suggested, while sustaining an M2-polarized protumorigenic phenotype. Transplanted tumors showed a more aggressive growth and faster polarization of the TAMs toward an M2 phenotype compared with primary tumors, a process dependent on the presence of few cotransplanted macrophages. Conclusions: Overall, we propose a new way for tumor-educated TAMs to contribute to glioma aggressiveness by long survival and stable protumorigenic features. These properties could have a relapse-supporting effect.